Reactivity of metals tethered to metal-organic frameworks - Young, Rosemary (2021)
The reactivity of solid-state materials differs from those in solution or gaseous states due to structure, surface and transport effects. While the reactivity of metal complexes in solution have been well explored, the study of well-defined solid-state metal complexes has been stymied by difficulties in characterisation and poor stability. Metal-organic frameworks (MOFs) provide a promising platform for the site-isolation, characterisation and reaction of such complexes. The controlled delivery of CO gas from photoactivated Mn(I) carbonyl complexes is desired for medical and chemical synthesis applications. A fac-tricarbonyl Mn(I) complex was tethered to the bis-pyrazole coordination site of L’ in MnMOF, [Mn3L2L’] (H2L = 4,4'-{methylenebis(3,5-dimethyl-1H-pyrazole-1,4-diyl)}dibenzoic acid), and found to undergo a series of solvent-induced isomerisations. The photoactivated decarbonylation pathway for MnMOF[Mn(CO)3X]Y (X,Y = Br- or solvent) was studied, involving the stepwise loss of the carbonyl ligands, with di- and mono-carbonyl intermediates observed by IR spectroscopy and photocrystallography. Exposure to environmental oxidising agents resulted in a proposed final Mn(II) decarbonylation product, which formed a Mn(II) carbonyl species when exposed to CO gas. MnMOF[Mn(CO)3X]Y was used as an ex-situ light-triggered source of CO gas for aminocarbonylation reactions, achieving high yields with low excesses of CO. Two other Mn(I) carbonyl metalated MOFs, UiO-67-bpy and DUT-5-bpy, were likewise tested, and achieved high yields, although with different efficiencies. This demonstrated the influence of structure, topology and particle size on the effectiveness of these CO sources. To examine the former, MnMOF was structuralised from sacrificial sol-gel-derived manganese oxide templates. The template structure was found to influence the kinetics of formation and macrostructural properties of the MOF crystals. Inorganic azides may react photochemically through a range of mechanisms, including the formation of highly reactive nitrene intermediates. As such, they are useful synthetic or catalytic intermediates. An azidocarbonyl Mn(I) molecular complex dissolved in tetrahydrofuran or dichloromethane was found to form a bridging isocyanate complex upon irradiation with light, while the same complex isolated within MnMOF showed different reactivities at different temperatures in the presence of a coordinating solvent. Isocyanate was formed at room temperature for bulk, matrixisolated samples, and at 190 K in a single crystal. At lower temperatures, decarbonylation occurred without formation of a nitrene. The site-isolation of palladium catalysts in MOFs has allowed for improved reactivities and selectivities, but few of these complexes have been structurally characterised through single-crystal X-ray diffraction techniques. Palladium halide complexes were tethered to MnMOF by post-synthetic metalation, but further investigations were hindered by the lability of the complexes and their propensity to form of pore-bound species, in addition to ligand-bound species, resulting in unpredictable metalation efficiencies. Finally, silver coordination polymers have demonstrated antibacterial behaviour, but the properties controlling their activity are not well understood. The dissolution behaviour of a sub-set of four silver coordination polymers, chosen to probe the relative impacts of coordination chemistry and topology, revealed that metal-ligand bond strength has the greatest impact on controlling silver ion release. The formation of composite materials with organic polymers attenuated the release of silver ions in waterwith the more water permeable polymer, polycaprolactone, allowing for greater silver release than polyethylene. All four coordination polymers showed antibacterial activity, albeit to different extents. For the reactions of metal complexes tethered to MOFs to be studied, the retention of long-range order and complex stabilities are the major barriers to characterisation. Judicious choice of a MOF host which permits changes in the coordination sphere of the metal, without loss of crystallinity, and site-isolation mitigates some of these challenges. In this work, it has been observed that environmental parameters such as temperature, light and exposure to air and moisture, all affect the reactions of metals tethered to MOFs. In addition, structural parameters of topology, morphology and structuralisation affect the utility of these materials.